The complex relationships among self-acceptance, perceived social support, drug use stereotype threat, and subthreshold depression in people with substance use disorder: exploring the mediating and buffering effects - Li, Yongqiu; Wang, Rufang; Liu, Jun; Li, Zuoliang; Zhou, Yinghua (Frontiers in Psychiatry, 2025)
IntroductionDepression levels are significantly higher among people with substance use disorder (SUD) than in the general population; however, studies on the level of subthreshold depression in this population are scarce. Research shows a significant correlation between self-acceptance and depression, with social support playing a key role in the process of recovery and social reintegration for people with SUD. This study aimed to explore the effects of self-acceptance, perceived social support, and stereotype threat of people with SUD on their subthreshold depression, as well as potential mediating and buffering effects.MethodsThis study was conducted from January-March 2024. 1068 drug addicts (548 males and 520 females) were recruited in Chengdu, Sichuan Province. After signing informed consent, their psychometric data were obtained using the Self-acceptance Questionnaire (SAQ), Perceived Social Support Scale (PSSS), Drug Use Stereotype Threat Scale (DSTS) and Center for Epidemiologic Studies Depression Scale(CES-D). Gender and group differences in relevant scale dimensions were explored. Linear regression models were used to assess the relationships between PSSS, SAQ, and DSTS scores and subthreshold depression in male and female participants. Bootstrap mediation effect tests were used to further test the mediation effect of drug use stereotype threat and perceived social support between self-acceptance and subthreshold depression. Line graphs were used to show the buffering effect of perceived social support on the relationship between self-acceptance and subthreshold depression in different groups.ResultsThe results showed that,gender, HIV-positive or not, education and monthly income level affect subthreshold depression in patients with SUD. Negative correlation between self-acceptance and subthreshold depression among SUD patients. Furthermore, perceived social support and substance use stereotypes threatmediated the relationship between self-acceptance and subthreshold depression, respectively, forming a parallel mediating relationship. Results exploring the buffering effect of perceived social support by subgroup showed that the buffering effect of perceived social support on subthreshold depression was most pronounced in the HIV-negative and and female groups. Social support, group stereotypes discrimination affect the mental health of sud patients.DiscussionOur study provides theoretical support for the alleviation of subthreshold depression among people with SUD, realizing that self-acceptance, perceived social support and reduction of drug use stereotype threat can be a psychoprotective factor for people with SUD.